Exogenous Spermidine Priming Mitigates the Osmotic Damage in Germinating Seeds of Leymus chinensis Under Salt-Alkali Stress - Hongna, Chen; Junmei, Shi; Leyuan, Tao; Xiaori, Han; Guolin, Lin; Xianguo, Cheng (Frontiers in Plant Science, 2021)
Spermidine (Spd) is known to protect macromolecules involved in physiological and biochemical processes in plants. However, it is possible that Spd also plays an osmotic regulatory role in promoting the seed germination of Leymus chinensis (L. chinensis) under salt-alkali stress. To investigate this further, seeds of L. chinensis were soaked in Spd solution or distilled water, and a culture experiment was performed by sowing the soaked seeds in saline-alkaline soils. The data showed that the Spd priming resulted in an increase of more than 50% in soluble sugar content and an increase of more than 30% in proline content in the germinating seeds. In addition, the Spd priming resulted in an increase of more than 30% in catalase activity and an increase of more than 25% in peroxidase activity in the germinating seeds and effectively mitigated the oxidative damage to the plasma membrane in the germinating seeds under salt-alkali stress. Moreover, the Spd priming of seeds affected the accumulation of polyamine (PA) and maintained the activities of macromolecules involved in physiological metabolism in germinating seeds exposed to salt-alkali stress. Furthermore, the Spd priming treatment increased the hydrogen peroxide (H2O2) level to more than 30% and the Ca2+ concentration to more than 20% in the germinating seeds, thus breaking the dormancy induction pathways in L. chinensis seeds through beneficial hormone enrichment. This study provides an insight into the Spd-mediated regulation pathway during exogenous Spd priming of L. chinensis seeds, which mitigates osmotic and oxidative damage and maintains the integrality of the cell lipid membrane. Thus, exogenous Spd priming increases PA oxidase activity and maintains the accumulation of H2O2. We found that the H2O2 beneficially affected the balance of Ca2+ and hormones, promoting the vigor and germination of L. chinensis in response to salt-alkali stress.